2015
DOI: 10.1287/mnsc.2014.2068
|View full text |Cite
|
Sign up to set email alerts
|

Goal Setting and Monetary Incentives: When Large Stakes Are Not Enough

Abstract: Document de Treball núm.13/5La sèrie Documents de treball d'economia de l'empresa presenta els avanços i resultats d'investigacions en curs que han estat presentades i discutides en aquest departament; això no obstant, les opinions són responsabilitat dels autors. El document no pot ser reproduït total ni parcialment sense el consentiment de l'autor/a o autors/res. Dirigir els comentaris i suggerències directament a l'autor/a o autors/res, a la direcció que apareix a la pàgina següent.A Working Paper in the Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 40 publications
4
65
1
1
Order By: Relevance
“…The field experiment also provides some interesting insights into the differences between self-chosen and assigned goals and on the effects of the difficulty of the goal [5]. While self-chosen and assigned goals led to the same increase in average productivity, they led to different distributions of outputs.…”
Section: Self-chosen or Assigned Goals And Accuracy Of Goal Settingmentioning
confidence: 97%
See 2 more Smart Citations
“…The field experiment also provides some interesting insights into the differences between self-chosen and assigned goals and on the effects of the difficulty of the goal [5]. While self-chosen and assigned goals led to the same increase in average productivity, they led to different distributions of outputs.…”
Section: Self-chosen or Assigned Goals And Accuracy Of Goal Settingmentioning
confidence: 97%
“…First, they are extrinsically motivated by the wages they receive, and second, they are intrinsically motivated to reach their personal goals. Consequently, goals provide a reference point against which workers can measure their satisfaction (utility) by dividing outcomes into gains, when the goal is attained, and losses, when output falls below the goal [2], [3], [4], [5]. In line with prospect SebaStian J. GoerG | Goal setting and worker motivation…”
Section: Positive Effects Of Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it relates to the literature highlighting the effectiveness of various forms of non-monetary incentives on workers motivation (Deci (1971); Frey and Jegen (2001) ;Gneezy, Meier, and Rey-Biel (2011)). Examples of effective non-monetary incentives are goals (Wu, Heath, and Larrick (2008); Goerg and Kube (2012); Gómez-Miñambres (2012) ;Corgnet, Gómez-Miñambres, and Hernán-Gonzalez (2015)), interpersonal ties (Bandiera, Barankay, and Rasul 2010), symbolic awards (Kosfeld and Neckermann (2011), authority (Fehr, Herz, and Wilkening (2013)) and autonomy (Falk and Kosfeld (2006)). We contribute to this literature by showing unique evidence of the role of moral support as a novel non-monetary incentive to increase workers performance.…”
Section: Related Literaturementioning
confidence: 99%
“…Research on goal setting states that a challenging goal set by the principal can boost the agent's performance (Wu et al, 2008;Corgnet et al, 2015). Besides, theoretical models have shown that personal goals could address self-control problems that stem from present-biased preferences Nafziger, 2009, 2011), and empirical evidence has shown that binding personal goals could be motivating and lead to high performance levels as compared to contracts that carry comparable monetary rewards (Dalton et al, 2015;Goerg and Kube, 2012).…”
Section: Introductionmentioning
confidence: 99%